2012
DOI: 10.3928/01477447-20111122-31
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoseptic Arthritis of the Shoulder Following Pneumococcal Vaccination

Abstract: Pseudoseptic arthritis is primarily described in rheumatoid arthritis and other systemic inflammatory conditions. To our knowledge, only 1 case report of pseudoseptic arthritis associated with intra-articular injection of a pneumococcal polyvalent vaccine (PPV) has been published. Here, a second case is presented in which a patient presented with swelling, pain, and erythema of the affected shoulder. A 59-year-old woman presented to the emergency department with a 3-day history of severe pain and decreased mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 7 publications
0
19
0
6
Order By: Relevance
“…The additional MRI findings in these prior reports included rotator cuff tendinosis and tendon tears. 5,9,10,12,15,16,20 Our case is unique in that progressive erosive changes were demonstrated along with an increase in severity of changes suggesting bursitis, synovitis, and adhesive capsulitis on serial examinations over a 6-month period. In addition, subsequent stabilization of osseous erosions was evident on radiographic follow-up 32 months later, after the resolution of symptoms.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The additional MRI findings in these prior reports included rotator cuff tendinosis and tendon tears. 5,9,10,12,15,16,20 Our case is unique in that progressive erosive changes were demonstrated along with an increase in severity of changes suggesting bursitis, synovitis, and adhesive capsulitis on serial examinations over a 6-month period. In addition, subsequent stabilization of osseous erosions was evident on radiographic follow-up 32 months later, after the resolution of symptoms.…”
Section: Discussionmentioning
confidence: 77%
“…Subsequently, there have been a few published case reports and small series for a total of 25 cases describing the MRI findings of prolonged postvaccination shoulder injury. 5,[9][10][11][12][13] Fourteen of the 25 cases documented the MRI findings of bursitis, 5,12,[14][15][16][17][18][19] and 10 cases demonstrated bone marrow edema in the humeral head, 5,[10][11][12]14,16,[18][19][20] 8 of which followed influenza vaccination. Only 4 previous cases have demonstrated bone erosion on MRI after vaccination, 10,11,19,20 3 of which followed influenza vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…2,11,12 In addition to the pain and decreased range of motion, one case report revealed that the shoulder dysfunction was accompanied by osteolysis and surface chondrolysis that may require surgical intervention; this was also associated with incorrect placement of the injection. 13 In an attempt to support this hypothesis, Lippert studied the deltoid fat pads through MRI imaging and showed that 5/8-in-, 7/8-in-, and 1-in-long needles led to overpenetration in 11%, 55%, and 61% of the pediatric population studied, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…2,[11][12][13] Given that the majority of primary and secondary causes of frozen shoulder are unknown, 11 there could be a yet undiscovered underlying cause leading to the presentation of our patients. However, to the best of our knowledge, vaccination was the cause of shoulder stiffness in our cases.…”
Section: Limitationsmentioning
confidence: 98%
“…One with quadrivalent human papilloma virus vaccine (Gardasil Ò ) 23 in which no additional clinical data were given and 2 24,25 with 23 valent pneumococcal polysaccharide vaccine (Pneumovax Ò ). The latter cases reported in females 59 and 76 years old respectively were diagnosed as pseudoseptic arthritis of the glenohumeral joint.…”
Section: Intra-articular Injectionmentioning
confidence: 99%